2021
DOI: 10.1186/s13012-021-01132-0
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing organizational readiness for implementation: constructing a typology of readiness-development strategies using a modified Delphi process

Abstract: Background Knowledge about the development of organizational readiness for implementation (ORI) is limited. ORI, referred to as the willingness and capacity of all relevant stakeholders to change practice, is critical for increasing the adoption rate of evidence-based practices and improving implementation outcomes. However, no methodology currently guides ORI’s enhancement or addresses differences in readiness needs across an organization. This study used the transtheoretical model (TTM) as a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 54 publications
3
7
0
Order By: Relevance
“…In our analysis, nine ERIC strategies were categorised as having no BCTs indicated in their description or were not targeting behaviour change for the implementation of an innovation. The results align with recent efforts to organise implementation strategies into categories related to their timing [40] and target [49]. In terms of timing, strategies such as assessing readiness and tailoring could be used to prepare for the execution of the innovation or to inform the selection of other strategies.…”
Section: Deconstructing High-level and Preparatory Strategiessupporting
confidence: 73%
See 2 more Smart Citations
“…In our analysis, nine ERIC strategies were categorised as having no BCTs indicated in their description or were not targeting behaviour change for the implementation of an innovation. The results align with recent efforts to organise implementation strategies into categories related to their timing [40] and target [49]. In terms of timing, strategies such as assessing readiness and tailoring could be used to prepare for the execution of the innovation or to inform the selection of other strategies.…”
Section: Deconstructing High-level and Preparatory Strategiessupporting
confidence: 73%
“…With limited information in the strategy description, it was not feasible to code an exhaustive list of all BCTs. A number of studies have highlighted that ERIC strategies vary in their level of specificity [40,41]. It has been suggested that taxonomies such as the ERIC compilation do not possess the granularity and specificity the BCT Taxonomy contains [27].…”
Section: Enhancing Levels Of Specificitymentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, some of the clusters in ERIC [ 40 ] are clearly directed towards the action target (e.g., Train and educate stakeholders or Support clinicians) , making the coding even more challenging. Our observations are in line with other studies that have highlighted some discrepancies concerning the level of detail across different ERIC strategies [ 7 , 54 , 55 ]. We also acknowledge that other ways of clustering ERIC strategies have been applied in other research initiatives to suit different study objectives [ 2 , 7 , 8 , 10 , 54 ].…”
Section: Discussionsupporting
confidence: 93%
“…For a more setting-specific application of the organizational readiness concept, the key factors of intervention implementation as identified in our multiple case study might also be useful for a readiness assessment. This readiness judgment should then be followed by a recommendation of strategies to enhance readiness before a co-creation process is conducted, for example, by identifying and preparing a champion [see the typology of readiness development strategies by Vax et al ( 62 )].…”
Section: Discussionmentioning
confidence: 99%